Increment a value in XSLT

2019-01-18 01:56发布

I'm reasonably new to xlst and am confused as to whether there is any way to store a value and change it later, for example incrementing a variable in a loop.

I'm a bit baffled by not being able to change the value of a after it's set doesn't make sense to me, making it more of a constant.

For example I want to do something like this:

<xsl:variable name="i" select="0" />
<xsl:for-each select="data/posts/entry">
    <xsl:variable name="i" select="$i + 1" />
    <!-- DO SOMETHING -->
</xsl:for-each>

If anyone can enlighten me on whether there is an alternative way to do this
Thanks

3条回答
【Aperson】
2楼-- · 2019-01-18 02:16

I ran into that myself two years ago. You need to do use recursion for this. I forget the exact syntax, but this site might help:

Tip: Loop with recursion in XSLT

The strategy works basically as follows: Replace for loop with a template "method". Have it recieve a parameter i. Do the body of the for loop in the template method. If i > 0 call the template method again (recursion) with i - 1 as parameter.

Pseudocode:

for i = 0 to 10:
   print i

becomes:

def printer(i):
   print i
   if i < 10:
      printer(i + 1)
printer(0)

Please note that using position() in a xsl:for-each (see other answers) can be simpler if all you want to do is have a variable increment. Use the kind of recursion explained here if you want a more complicated loop / condition.

查看更多
叛逆
3楼-- · 2019-01-18 02:17

You can use the position() function:

<xsl:for-each select="data/posts/entry">
  <xsl:text>
    Postion: '
  </xsl:text>
  <xsl:value-of select = "position()" />
  <xsl:text>
    '
  </xsl:text>
  <!-- DO SOMETHING -->
</xsl:for-each>
查看更多
疯言疯语
4楼-- · 2019-01-18 02:30

XSLT is a functional language and among other things this means that variables in XSLT are immutable and once they have been defined their value cannot be changed.

Here is how the same effect can be achieved in XSLT:

<xsl:stylesheet version="1.0"
 xmlns:xsl="http://www.w3.org/1999/XSL/Transform">
 <xsl:output omit-xml-declaration="yes" indent="yes"/>
 <xsl:strip-space elements="*"/>

 <xsl:template match="/">
   <posts>
    <xsl:for-each select="data/posts/entry">
        <xsl:variable name="i" select="position()" />
        <xsl:copy>
         <xsl:value-of select="concat('$i = ', $i)"/>
        </xsl:copy>
    </xsl:for-each>
   </posts>
 </xsl:template>
</xsl:stylesheet>

when this transformation is applied on the following XML document:

<data>
 <posts>
  <entry/>
  <entry/>
  <entry/>
  <entry/>
  <entry/>
 </posts>
</data>

the result is:

<posts>
    <entry>$i = 1</entry>
    <entry>$i = 2</entry>
    <entry>$i = 3</entry>
    <entry>$i = 4</entry>
    <entry>$i = 5</entry>
</posts>
查看更多
登录 后发表回答